Prophylactic cranial irradiation for extensive-stage small-cell lung cancer: an evolving view - Ludmir, Ethan B.; Lin, Steven H. (Translational Cancer Research; Vol 6, Supplement 6 (August 29, 2017): Translational Cancer Research, 2017)
Small-cell lung cancer (SCLC) is an aggressive malignancy with high rates of brain metastasis (BM) and poor long-term survival (1,2). It is estimated that nearly 80% of SCLC patients will develop brain metastases at some point during their treatment course, and up to 15% of SCLC patients will have asymptomatic brain metastases at diagnosis (1,3,4). Against this backdrop, there have been multiple efforts to assess the role of prophylactic cranial irradiation (PCI) in the treatment of SCLC, both to decrease the incidence of BM as well as improve other disease-related outcomes, including overall survival (OS). Meta-analyses have demonstrated that patients with complete response (CR) after initial chemotherapy (or chemoradiation) have decreased incidence of BM and improved OS with the addition of PCI (5,6).